2012
DOI: 10.1039/c2ce25321f
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition between cubic and monoclinic polymorphs of the tetracyanoethylene crystal: the role of temperature and kinetics

Abstract: Prediction of the relative stabilities and phase transition behavior of molecular crystalline polymorphs is highly coveted as distinct phases can possess different physical and chemical properties while having similar energies. Crystalline tetracyanoethylene (TCNE, C 6 N 4 ) is known to exhibit rich solid state phase behavior under different thermodynamic conditions, as demonstrated by a wealth of experimental studies on this system. Despite this fact, the role of temperature and kinetics on the phase diagram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 50 publications
2
27
0
Order By: Relevance
“…Furthermore, it was shown by Reilly and Tkatchenko that a high‐level vdW‐inclusive DFT method is able to describe the relative enthalpy and entropy of the two known polymorphs of aspirin correctly, offering a resolution for a long‐standing controversy regarding the metastability of form‐II aspirin . In addition, Schatschneider et al have shown that vdW‐inclusive DFT is able to describe temperature‐induced phase transitions between molecular crystal polymorphs of tetracyanoethylene in excellent agreement with experimental data …”
Section: Where We Are—back To Realitymentioning
confidence: 99%
“…Furthermore, it was shown by Reilly and Tkatchenko that a high‐level vdW‐inclusive DFT method is able to describe the relative enthalpy and entropy of the two known polymorphs of aspirin correctly, offering a resolution for a long‐standing controversy regarding the metastability of form‐II aspirin . In addition, Schatschneider et al have shown that vdW‐inclusive DFT is able to describe temperature‐induced phase transitions between molecular crystal polymorphs of tetracyanoethylene in excellent agreement with experimental data …”
Section: Where We Are—back To Realitymentioning
confidence: 99%
“…However, these works are related to single phase materials and not for heterojunctions with interface formed with different chemical compounds, phases and crystalline lattices tensions. It has been reported in several works that physical chemistry parameters deriving from growth surface between materials [18] and from synthesis procedure [19,20] can promote changes in crystalline phase stability, and hence changes on energy emission behavior. Different synthesis have been proposed in order to modulate the heterostructure properties, but, traditional methods are generally complex [10,14,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…To incorporate these long‐range electron correlation effects within DFT, significant progress has been made by using the standard C 6 / R 6 pairwise additive expression for the dispersion energy 57. Indeed, DFT with pairwise dispersion terms can yield accurate results when the energy differences between molecular crystal polymorphs are sufficiently large 810. Notably, Neumann et al.…”
mentioning
confidence: 99%